2003
DOI: 10.1046/j.1471-6712.2003.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer patients' experiences of lymphoedema

Abstract: The aim of this study was to explore employed women's experiences of light or moderate arm lymphoedema following breast cancer treatment in order to gain a deeper understanding of this phenomenon. Twelve women took part in a semistructured interview. A qualitative method with a phenomenological approach was applied to analyse data. In order to integrate the experiences in the everyday life of the women, a critical incident method was used. The findings indicate that there are many different practical and psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
1
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 30 publications
6
63
1
7
Order By: Relevance
“…Similarly, Hare's study 49 demonstrated high quality especially in her reporting of analysis and results. Likewise, Johansson et al 30 adequately achieved the criteria. Radina and Armer 50 strongly established the significance of their study question.…”
Section: Methodologic Problemsmentioning
confidence: 91%
See 3 more Smart Citations
“…Similarly, Hare's study 49 demonstrated high quality especially in her reporting of analysis and results. Likewise, Johansson et al 30 adequately achieved the criteria. Radina and Armer 50 strongly established the significance of their study question.…”
Section: Methodologic Problemsmentioning
confidence: 91%
“…Of the four qualitative studies, two 30,48 utilized a phenomenologic approach, semistructured interviews, and directed questions to elicit specific concerns and to promote understanding of women with SLE. Hare 49 used data gathered from audio recordings of four focus groups, and analyzed the data using a grounded theory approach.…”
Section: Methodologic Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Impact of lymphedema to patients' physical and psychological health can be enormous, with long lasting and often permanent sequelae to their quality of life [19,20].…”
Section: Discussionmentioning
confidence: 99%